Relationship between infantile mother preference and neural regions activated by maternal contact in C57BL/6 mice. (May 2022) - Shimizu, Kie; Tanaka, Rieko; Iso, Manami; Harada, Kazuki; Tsuboi, Takashi; Kondo, Yasuhiko; Nakamura, Kazuaki
Highlights: C57BL/6 mouse pups at PND 16 exhibited different preferences to the mother/novel dam. Differences in mother preference were not related to sex, weight, or litter size. Neural activity in the ACC and BNST may be associated with the preference of pups for their mothers. Abstract: Mutual attachment between mother and pup is important to enable the mother to care for her pup and for the pup to receive care from its mother. Pups eventually leave their mothers, which is also very important to their growth. The mechanism of preference by which pups transfer attachment from their mother to others remains unknown. In this study, we assessed mother/novel dam preferences and examined the brain regions associated with the regulation of this preference in C57BL/6 mice pups. We found that C57BL/6 mice pups had variety in their mother/novel dam preferences at 16 days old. This variety was not related to the sex of the pups, their weight, or the litter size. In order to clarify the brain mechanisms responsible for this variety, we examined the relationship between mother/novel dam preference and neuronal activation induced by contact with the mother. We found that pups exhibiting novel dam preference had higher neural activity in the anterior cingulate cortex (ACC) and bed nucleus of the stria terminalis (BNST) when exposed to their mother. These results suggest that ACC and/or BNST neural activity may be associated with mother/novel dam preferences in infant mice.